EFEK PENGGUNAAN PUPUK ORGANIK DAN INOKULAN MIKROBATERHADAP PERTUMBUHAN JATI SUPER (Tectona grandis L.f.) PADA LAHAN BEKAS TAILING POND PENAMBANGAN EMAS DI CIKOTOK - Dyah Supriyati; Dwi Agustiyani (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Experiment using organic fertilizer and microbial community to support the growth of Tectona grandis L.f in the cyanide contaminated-soil has been conducted in gold tailing pond Cikotok. Microbes used in this experiment were mixed of cyanide degradingbacteria,Nitrogen fixing-bacteria, and Phosphat solubilizing-bacteria. The results show that the microbes given in the Tectona grandis L.f plantation was significantly supporting the growth of the plants and reduced cyanide from the contaminated soil, but did not influence the microbe population of the soil.Key word: Phytoremediation, Cyanide, Tectona grandis L.f.